2007
DOI: 10.4049/jimmunol.178.3.1923
|View full text |Cite
|
Sign up to set email alerts
|

Selective Inhibition of IκB Kinase Sensitizes Mantle Cell Lymphoma B Cells to TRAIL by Decreasing Cellular FLIP Level

Abstract: In an attempt to circumvent the intrinsic resistance of mantle cell lymphoma (MCL) cells to apoptosis, we have analyzed their sensitivity to the extrinsic apoptotic signal triggered by TRAIL. We show here that TRAIL can trigger apoptosis in a majority of MCL cell lines and primary cultures, irrespective of receptor levels, Bcl-2 family members, or caspase regulator expression. MCL sensitivity to TRAIL was closely linked to the activity of the NF-κB p50 factor and to the consequent expression of cellular FLIP (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(64 citation statements)
references
References 35 publications
3
61
0
Order By: Relevance
“…1 In this regard, several classical transduction pathways involved in cancer (for example, NF-kB, Notch, PI3K/AKT/mTOR, and Wnt) are constitutively active in different subsets of MCLs. 1,[3][4][5][6] Here, we show that ZEB1, a transcription factor that has a key role in EMT and carcinoma progression, is found in the same subset of primary MCLs that express bcatenin. ZEB1 expression in MCL cells is dependent on Wnt as further activation of Wnt signaling upregulates ZEB1, whereas interference of the pathway -either by knockdown of b-catenin or treatment with Wnt inhibitor salinomycin -downregulates it.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…1 In this regard, several classical transduction pathways involved in cancer (for example, NF-kB, Notch, PI3K/AKT/mTOR, and Wnt) are constitutively active in different subsets of MCLs. 1,[3][4][5][6] Here, we show that ZEB1, a transcription factor that has a key role in EMT and carcinoma progression, is found in the same subset of primary MCLs that express bcatenin. ZEB1 expression in MCL cells is dependent on Wnt as further activation of Wnt signaling upregulates ZEB1, whereas interference of the pathway -either by knockdown of b-catenin or treatment with Wnt inhibitor salinomycin -downregulates it.…”
Section: Discussionmentioning
confidence: 63%
“…In that regard, chromosomal alterations and nongenetic modifications resulting in the constitutive activation of pro-oncogenic signals (for example, NF-kB, Notch, PI3K/AKT/mTOR, and Wnt) and/or deregulation of DNA repair and apoptotic pathways and genes (for example, AKT, BCL2, MCL1) have been found in subsets of MCLs, providing additional levels of plasticity in the genesis and progression of the disease. 1,[3][4][5][6][7][8][9][10][11] Of particular interest is the canonical Wnt pathway that has a crucial role in normal hematopoiesis and whose aberrant activation, long known to drive tumorigenesis in solid tumors, has also been involved in a number of hematological malignancies, including MCLs. 3,5,6,[12][13][14][15][16][17][18][19]20 In addition to gain-of-function mutations of intracellular components of the Wnt pathway, overexpression of Wnt receptors and ligands or downregulation of Wnt inhibitors through nongenetic modifications are also common.…”
mentioning
confidence: 99%
“…Recently, down-regulation of c-FLIP has been proposed to contribute to the sensitization of TRAIL-induced apoptosis by MG-132 or IκB kinase inhibitor [21,22]. We found that two isoforms of c-FLIP, c-FLIP L and c-FLIP S , were markedly decreased in a dosedependent manner in various cancer cells, including Caki, Hep3B, SK-Hep1, and Huh7 cells, treated with Wit A (Fig.…”
Section: Down-regulation Of C-flip Also Contributes To Wit A-stimulatmentioning
confidence: 62%
“…We used the IKK inhibitor BMS-345541 (33,34). As expected, NF-κB inhibition by BMS-345541 potentiated cell death induced by TRAIL as well as by TNF-α in HCT116, HT1080/ DR4 (Fig.…”
Section: Prmt5 Contributes To Trail Resistance By Activating Nf-κb Simentioning
confidence: 69%